Managing Information about a Romantic Partner's Relationship History: An Application of the Theory of Motivated Information Management. Issue 2 (14th March 2016) - Lancaster, Alexander L.; Dillow, Megan R.; Ball, Hannah; Borchert, Katherine; Tyler, William J. C.
ABSTRACT: Using the theory of motivated information management (TMIM), this study explored how individuals manage information about romantic partners' past relationships, a typically taboo topic (Baxter & Wilmot, 1985). A sample ( N = 146) of undergraduate students currently involved in romantic relationships was used to test TMIM's predictions regarding cognitive, emotional, and communicative processes involved in information-management decisions regarding a partner's previous relationships. The hypothesized models were supported for negative emotions (i.e., anger and fear) but not for happiness as a representative positive emotion. Further, efficacy emerged as a significant mediator of the relationships between the negative emotions and information-management strategies and of the associations between outcome assessments and information-management strategies. Implications and future research directions are discussed.